DERCA on-line: gestão acadêmica corporativa e processamento colaborativo de informações acadêmicas - Dias, Evandro Dotto (2010)
According to data from the first half of 2010, the Federal University of Santa Maria has 21.932 students enrolled in undergraduate and graduate courses. The management and technological improvement proposal for the project "DERCA ON-LINE: CORPORATIVE ACADEMIC MANAGEMENT promotes flexible decision, seeking improvements in collaborative performance. Corporative Academic Management (CAM) is correlated with the Knowledge Management in UFSM, technological innovation, organizational learning and management of academic production. The institution must observe the capability of their end product (knowledge), and thus make it competitive for the academic market and business in order to achieve promotion of public policies and attract resources from the private sector. The business process must be applied to the process of academic research and academic management as exemplified in the model of Academic Management for Scientific Production Enterprise (GAPCC). One of the goals of this work is to establish within the Federal University of Santa Maria a set of digital authenticated documents and files and their recognition as official documents. The Corporate Education (UFSM Corporate) within the framework of the Federal University of Santa Maria can become a set of practices "training of the body" facing the effective implementation of routines for the academic and administrative and academic system as a whole and be aligned with the Institutional planning within a continuous learning process.